GLOBAL OPTICAL MODEL POTENTIAL PARAMETERS FOR PROTON SCATTERING ON 6, 7Li AND 10, 11B NUCLEI. - Burtebayev, N.; Burtebayeva, J. T.; Urkinbayev, A. R.; Amar, A.; Hamada, Sh.; Sakuta, S. B. (Recent Contributions to Physics, 2011)
Analysis of the elastic scattering of protons on 6,7Li and on 10,11B nuclei has been done in the framework of the optical model at the beam energies up to 50 MeV. Differential cross sections for the 6,7Li and 10, 11B were measured over the proton laboratory–energy range from 400 to 1200 KeV, and combined with published differential cross sections for proton elastically scattering from 6,7Li and 10,11B between 0.5 MeV and 50 MeV, are analyzed in terms of the Optical Model. Depending on the measured data by us and literature data, we could enhance the potential parameters. Linear relationship between volume real potential (V0) and proton energy (Ep) have been obtained. Also, surface imaginary potential WD is proportional to the proton energy (Ep) in the range 0.700 and 14 MeV. Optical model parameters are found characterized volume integral per nucleon pair for the real and imaginary potentials, JR and Jw. Good agreement between theoretical and experimental data in whole range. We attempt to make empirical relations describing the energy dependence of the opticalmodel potential.